Weightages and income sharing ratio practice for profit distribution in Islamic banks: Bangladesh scenario - Kawsar, Najmul Haque; Hassan, Aznan; Haron, Razali (Accounting and Auditing Organisation of Islamic Finance Institutions (AAOIFI), 2023)
The article first explores the weightages system, a specific profit calculation method for profit distribution on deposits taken under Mudarabah, which has been widely used since Bangladesh started Islamic banking in 1983. There has been a growing discussion about whether this approach fully adheres to Islamic banking principles. We then explore an alternative system known as the Income Sharing Ratio (ISR) method, which some banks have started to implement as it is claimed to be aligned more closely with Islamic principles. Using textual and discourse analysis and relevant AAOIFI standards, the paper compares the practices of both calculation methods for Mudarabah based deposits profits within the Bangladeshi Islamic banking industry context. The analysis suggests that the current prevalent practice of the weightages in Bangladesh needs improvement, and the ISR approach can either replace it or help improve it. The authors offer specific actionable recommendations to stakeholders for better adherence to Islamic principles when processing Mudarabah transactions.